Nadzór nad rynkiem usług płatniczych w Polsce w kontekście najnowszych zmian prawa polskiego i unijnego - Zalcewicz, Anna (Kwartalnik Prawa Publicznego, 2012)
The purpose of the article is the analysis of legal aspects of supervision over the payment services market in the contexts of the newest changes of Polish and EU Law. The scope of the analysis concentrates on European Union law concerning the payment services – mainly on the Directive 2007/64/EC – and on Polish legal regulations – mainly on the Act of 19th of August 2011 on Payment Services as well as on the Act of 21st of July 2006 on the Supervision over the Financial Market. The author analysis in details the principles of supervision carried out by the Polish Financial Supervision Authority with reference to business conduct of the providers of payment services, the aims of supervision, powers and competences of the Financial Supervision Authority, supervision costs, as well as the influence of external bodies on the financial markets supervision.